Hubungkan Komunikasi Terapeutik Perawat dengan Kepuasan Pasien di Rawat Inap - Serli Nurfitriani; Erna Hamidah; Hadi Abdillah (Universitas Malahayati Lampung, 2025)
ABSTRACT Therapeutic communication is communication that is consciously planned with the aim of providing healing for the patient. Lack of knowledge of nurses in implementing therapeutic communication, level of education, attitudes of nurses, and the environment can influence patient dissatisfaction when receiving the nursing care that will be provided. The relationship of mutual trust between nurses and patients that is formed through therapeutic communication is a tool that plays a very important role in improving the patient's healing process. The aim of this research was to determine the relationship between nurses' therapeutic communication and patient satisfaction at the Betha Medika Hospital. This type of research is quantitative, correlational with a cross-sectional design, the sampling technique uses an incidental sampling method with a sample size of 85 respondents. The data collection technique uses an analytical questionnaire using the Chi-square test. The research results showed that 74 (87.1%) nurses had carried out therapeutic communication, while 11 (12.9%) nurses had not carried out therapeutic communication. The Chi-Square test shows a p-value of 0.000 0.05, which means there is a relationship between nurses' therapeutic communication and patient satisfaction. The conclusion from this research is that there is a relationship between nurse therapeutic communication and patient satisfaction in inpatient care. Keywords: Therapeutic Communication, Patient Satisfaction ABSTRAK Komunikasi terapeutik adalah komunikasi yang direncanakan secara sadar dengan tujuan untuk memberikan kesembuhan bagi pasien. Kurangnya pengetahuan perawat dalam menerapkan komunikasi terapeutik, tingkat pendidikan, sikap perawat, lingkungan dapat mempengaruhi ketidakpuasan pasien ketika menerima asuhan keperawatan yang akan diberikan. Hubungan saling percaya antara perawat dan pasien yang terbentuk melalui komunikasi terapeutik merupakan alat yang sangat berperan untuk meningkatkan proses penyembuhan pasien. Tujuan penelitian ini untuk mengetahui hubungan komunikasi terapeutik perawat dengan kepuasan pasien di rawat inap Rs.Betha Medika. Jenis penelitian ini kuantitatif kolerasional dengan desain cross-sectional, Teknik pengambil sampel dengan metode acidental sampling dengan jumlah sampel 85 responden. Teknik pengumpulan data menggunakan kuesioner analisis yang digunakan uji Chi-square. Hasil penelitian menunjukkan perawat sudah melakukan komunikasi terapeutik sebanyak 74 (87.1%), sedangkan perawat yang tidak komunikasi terapeutik sebanyak 11 (12.9%). Uji Chi-Square menunjukkan nilai p-value 0,000 0,05 yangbearti menunjukan ada hubungan antara komunikasi terapeurik perawat dengan kepuasan pasien. Kesimpulan dari penelitian ini ada hubungan komunikasi terapeutik perawat dengan kepuasan pasien di rawat inap. Kata Kunci: Komunikasi Terapeutik, Kepuasan Pasien